2008
DOI: 10.1051/fruits:2008017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of poultry manure and harvest season on juice quality of yellow passion fruit (Passiflora edulisvar.flavicarpaDeg.) in the sub-humid zone of Nigeria

Abstract: Impact of poultry manure and harvest season on juice quality of yellow passion fruit (Passiflora edulis var. flavicarpa Deg.) in the sub-humid zone of Nigeria. Abstract-Introduction. The production of high quality fruit juice involves several cultural inputs. Among other factors, fruit quality attributes are influenced by the cultivar, the climate, the harvesting time and soil fertility. Particularly, the soil fertility has a significant effect on the nutritional characteristics of the juice. Good practice as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 15 publications
8
20
0
Order By: Relevance
“…In the current study, application of poultry manure increased most of the nutritional properties of the 'Nsukka Yellow' pepper. Significant effect of poultry manure rate on the nutrient quality of pepper is also supported by an earlier study on passion fruits (in the same location), which showed that nutritional quality of the juice varied with poultry manure rate (Ani and Baiyeri, 2008).…”
Section: Pc2supporting
confidence: 66%
“…In the current study, application of poultry manure increased most of the nutritional properties of the 'Nsukka Yellow' pepper. Significant effect of poultry manure rate on the nutrient quality of pepper is also supported by an earlier study on passion fruits (in the same location), which showed that nutritional quality of the juice varied with poultry manure rate (Ani and Baiyeri, 2008).…”
Section: Pc2supporting
confidence: 66%
“…And although the plant is an efficient nutrient miner owing to its deep and extensive root system, growth and yields can be optimized by application of organic or inorganic fertilizers (Palada and Chang, 2003). Generally produce quantity and quality is enhanced with application of fertilizers (Ani and Baiyeri, 2008). Ramachandran et al (1980) achieved higher yields with organic fertilizer than growing Moringa without fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…Passion fruit has its unique properties. Yellow passion fruit consumed mainly as juice in many parts of the world, is a new crop in Nigeria [20]. It is exploited for its economic importance due to the presence of volatile compounds and a comparatively high acid content, which are responsible for its characteristic exotic flavor and aroma [21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…This study could also enhance the cultivation of passion fruit in Nigeria and provide employment. Passion fruit cropping offers a revenue earning opportunity for developing countries like Nigeria with an emerging economy [20]. Therefore, the research was aimed to produce acceptable yoghurt flavoured with two accessions of passion fruit (pulp and skin) and evaluate its quality.…”
Section: Introductionmentioning
confidence: 99%